Omni-channel service operations: Building technology-based business networks - Reis, João Carlos Gonçalves dos (2017)
This article investigates how omni-channel services operations are building technology-based business networks. It uses a case study research, which includes multiple sources of data collection for triangulation purposes, to study a real-life phenomenon. The results suggest that omni-channel companies are changing their landscape to business networks, looking for competitive advantages over their rivals. But this move incorporates new challenges, as it requires a transition based on operations management to allow these firms to adapt their processes and channels, in order to be able to collaborate in a heterogeneous network of firms. Another possible solution is the integration of innovation technologies that are enabling the combination of firm capabilities to underpin collaborative relationships. Previous research also suggests that service operations management in an omni-channel services context is largely unaddressed, as this discipline is essential for the edification of technology-based business networks. Thereby, this article provides real-life statements and examples of firms that are moving their service operations into a business network paradigm. Subsequently, since omni-channel services are multidisciplinary in nature, these exploratory results represent a fruitful opportunity for future research to involve other disciplines than service operations.